Modification of Low Refractive Index Polycarbonate for High Refractive Index Applications. (11th October 2009) - Suri, Gunjan; Jha, Gouri Shankar; Seshadri, Geetha; Khandal, Rakesh Kumar
Abstract : Polycarbonates and polythiourethanes are the most popular materials in use today, for optical applications. Polycarbonates are of two types which fall in the category of low refractive index and medium refractive index. The present paper describes the conversion of low refractive index polycarbonates into high refractive index material by the use of a high refractive index monomer, polythiol, as an additive. Novel polycarbonates, where the properties of refractive index and Abbe number can be tailor made, have been obtained. Thermal studies and refractive index determination indicate the formation of a new polymer with improved properties and suitable for optical applications.